HPLC-UV Method Development and Validation for Vitamin D3 (Cholecalciferol) Quantitation in Drugs and Dietary Supplements - I. E. Shohin; E. A. Malashenko; Yu. V. Medvedev; M. N. Bogachuk; S. A. Kulakov; M. A. Paleeva (Разработка и регистрация лекарственных средств, 2021)
ErratumIntroduction. An inadequate diet and living in the northern regions can lead to a lack of vitamin D3 and the development of diseases, including a decrease in immunity. To compensate for the lack of vitamin D, vitamin drugs are used that contain vitamin D in one of its active forms (usually in the form of cholecalciferol, vitamin D3).Aim. To develop and validate HPLC-UV method for the determination of vitamin D3 in vitamin drugs and to evaluate the content of cholecalciferol in selected drugs anddietary supplements presented in the Russian Federation.Materials and methods. Determination of vitamin D3 was carried out by HPLC with UV detection at a wavelength 266 nm. Sample preparation of vitamin drugs was carried out by extraction with methanol (for liquid dosage forms based on aqueous or triglyceride solutions) and extraction with an aqueous-methanol solution (for solid dosage forms based on water-soluble substances with vitamin D3) in a ratio of 2 to 8 (water-methanol).Results and discussions. The analysis methodology for the parameter "Vitamin D3 (cholecalciferol) content" in vitamin dosage forms by HPLC was validated according to the following validation parameters: specificity; accuracy; precision; linearity; range.Conclusion. The analysis methodology for the parameter "Vitamin D3 (cholecalciferol) content" in vitamin dosage forms by HPLC was developed. The method was validated according to the following validation parameters: specificity; accuracy; precision; linearity; range. The range of the method was 9,5–38 μg/ml. The method was used to determine vitamin D3 in vitamin drugs based on water-soluble forms of vitamin D3, in the form of aqueous solutions and form of fatty acids triglyceridessolutions.